4x + 6 -x(2x+3) > (x-2) (4x+5)
Răspunsuri la întrebare
Răspuns de
0
4x+6-x(2x+3)>(x-2)(4x+5)<=>-2xpatrat-3x+4x+6>4xpatrat+5x-8x-10<=>-2xpatrat-4xpatrat-3x-4x-5x+8x>-10-6
-6xpatrat+4x>-16
-x(6x-4)<=>
x=0 sau 6x-4=0
x=-4:6=0,(6)
a,(6)>-16
-6xpatrat+4x>-16
-x(6x-4)<=>
x=0 sau 6x-4=0
x=-4:6=0,(6)
a,(6)>-16
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Biologie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă
Istorie,
9 ani în urmă